Efficacy and safety of iscalimab, a novel anti-CD40 monoclonal antibody, in moderate-to-severe myasthenia gravis: A phase 2 randomized study - Gomez-Mancilla, Baltazar; Meriggioli, Matthew N.; Genge, Angela; Roubenoff, Ronenn; Espié, Pascal; Dupuy, Cyrielle; Hartmann, Nicole; Pezous, Nicole; Kinhikar, Arvind; Tichy, Mia; Dionne, Annie; Vissing, John; et al. (Journal of clinical neuroscience, 2023)
Background - Increased morbidity in many patients with myasthenia gravis (MG) on long-term immunosuppression highlights the need for improved treatments. The aim of this study is to investigate the safety and efficacy of iscalimab (CFZ533), a fully human anti-CD40 monoclonal antibody, in patients with moderate-to-severe MG receiving standard-of-care (SoC) therapies. - Methods - In this double-blind, placebo-controlled phase 2 study, symptomatic patients (n = 44) despite SoC were randomized 1:1 to receive intravenous iscalimab (10 mg/kg; n = 22) or placebo (n = 22) every 4 weeks for 6 doses in total. Patients were followed up for 6 months after the last dose. The total duration of the study was 52 weeks. - Results - In total, 34 of 44 patients (77.3 %) completed the study. The primary endpoint, Quantitative MG score, did not change significantly between baseline and week 25 for iscalimab (median [90 % CI], −4.07 [−5.67, −2.47]) versus placebo (−2.93 [−4.53, −1.33]); however, non-thymectomized patients (n = 29) showed more favorable results (iscalimab, −4.35 [−6.07, −2.64] vs placebo, −2.26 [−4.16, −0.36]). A statistically significant difference between iscalimab and placebo groups was observed in MG Composite score (adjusted mean change: −4.19 [−6.67, −1.72]; p = 0.007) at week 13, and MG-Activities of Daily Living score (−1.93 [−3.24, −0.62]; p = 0.018) at week 21. Adverse events were comparable between the iscalimab (91 %) and placebo (96 %) groups. - Conclusion - Iscalimab showed favorable safety and improvements compared with placebo in non-thymectomized patients with moderate-to-severe MG. It did not show any protective effect in patients with moderate-to-severe MG.